Antibiotic resistance, antimicrobial residues and bacterial community composition in urban wastewater - Ana Novo (2013)
This study was based on the hypothesis that the occurrence of antimicrobial residues and antibiotic resistant bacteria in the sewage could be correlated with the structure and composition of the bacterial community and the antibiotic resistance loads of the final effluent. Raw and treated wastewater composite samples were collected from an urban treatment plant over 14 sampling dates. Samples were characterized for the i) occurrence of tetracyclines, penicillins, sulfonamides, quinolones, triclosan, arsenic, cadmium, lead, chromium and mercury; ii) antibiotic resistance percentages for tetracycline, sulfamethoxazole, ciprofloxacin and amoxicillin and iii) 16S rRNA gene-DGGE patterns. The data of corresponding samples, taking into account the hydraulic residence time, was analyzed using multivariate analysis. Variations on the bacterial community structure of the final effluent were significantly correlated with the occurrence of tetracyclines, penicillins, sulfonamides, quinolones and triclosan in the raw inflow. Members of the class Epsilonproteobacteria presented positive correlations with those antimicrobials, whereas negative correlations were observed with Beta and Gammaproteobacteria and Firmicutes. Antibiotic resistance percentages presented different trends of variation in heterotrophs/enterobacteria and in enterococci, varied over time and after wastewater treatment. Antibiotic resistance was positively correlated with the occurrence of tetracyclines residues and high temperature. A relationship between antibiotic residues, bacterial community structure and composition and antibiotic resistance is demonstrated. Further studies, involving more wastewater treatment plants may help to elucidate this complex relationship.